Rhetorica revificata : retoriikan paluu / paluu retoriikkaan. - Lehtonen, Tuomas M. S. (1991)
Rhetorica revifacata - history and concepts of the rhetoric.
Summary: Rhetorica revifacata - history and concepts of the rhetoric.
Keywords: diskurssianalyysi; semantiikka; tekstianalyysi; puheet; diskursanalys; semantik; textanalys; tal (föredrag)